KETERKAITAN INSIDER OWNERSHIP DAN PREDIKSI KINERJA PERBANKAN DI BURSA EFEK INDONESIA - Sahala Manalu; Norman Sitinjak (Jurnal Keuangan dan Perbankan, 2012)
Insider ownership in banking business had two different roles, namely as both owner and manager of thebusiness at the same time. As managers, they were given the right of bank ownership in the hope of improvingbanking performance. With insider ownership, managers had greater rights to make decisions and also had abroader responsibility for decisions taken as they now shared the business risks. They also had greater controlover the banks where they worked, such that they had access to strengthen their position in their respectivebanks. Explanatory variables used in this study was insider ownership, while the dependent variable consistedof the CAR (Capital Adequacy Ratio), ROA (Return on Asset), BOPO (compared to Operating Income OperatingExpenses), and the ratio NPLgross (Non-Performing Loans gross). Using a statistical method PLS(Partial Least Square), the results showed that insider ownership could predict the performance of banks interms BOPO and NPLgross, but could not predict the CAR and ROA.